1999
DOI: 10.1165/ajrcmb.21.5.3755
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Gene Transfer to the Airway Regulates Allergic Mucosal Sensitization in Mice

Abstract: The objective of this study was to investigate the effect of airway gene transfer of interleukin (IL)-10, a cytokine with potent anti-inflammatory and immunoregulatory activities, on allergic mucosal sensitization. We used a recently described murine model that involves repeated exposures to aerosolized ovalbumin (OVA), daily for 10 d, in the context of granulocyte macrophage colony-stimulating factor (GM-CSF) expression in the airway environment achieved by intranasal delivery of a replication-deficient adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(88 citation statements)
references
References 52 publications
10
77
1
Order By: Relevance
“…Although our AR and inflammation responses generally agree with those of prior studies (30,31,34), they are not consistent with one study in which IL-10 Ϫ/Ϫ mice demonstrated significantly decreased BAL macrophage counts and increased eosinophilia and AR, as compared with the C57 mice (41). Those responses were consistent with what would be expected with a lack of IL-10 as an anti-inflammatory cytokine and are in agreement with phenotypic expectations that would come from human data demonstrating a lack of IL-10 production in asthmatics (7,8).…”
Section: Critique Of Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Although our AR and inflammation responses generally agree with those of prior studies (30,31,34), they are not consistent with one study in which IL-10 Ϫ/Ϫ mice demonstrated significantly decreased BAL macrophage counts and increased eosinophilia and AR, as compared with the C57 mice (41). Those responses were consistent with what would be expected with a lack of IL-10 as an anti-inflammatory cytokine and are in agreement with phenotypic expectations that would come from human data demonstrating a lack of IL-10 production in asthmatics (7,8).…”
Section: Critique Of Methodssupporting
confidence: 91%
“…Earlier studies have shown that elevations in Penh are correlated with eosinophilia in BALB/c mice (37); however, this association has been reported recently to be weak or absent, and there has been some controversy as to whether Penh can accurately reflect alterations in airway responsiveness in C57 mice (38,39). Our data suggest that alterations in AR associated with AI were consistent with expectations of airway hyporesponsiveness in IL-10 Ϫ/Ϫ mice, relative to their C57 IL-10-sufficient counterparts (30,31,33,34). Although we acknowledge some limitations to the Penh technique, we agree with the assertion by DeLorme and Moss (40) that the choice of the Penh measurement should be linked to the study objective and the ability to track alterations in AR previously verified by more invasive measures of lung resistance.…”
Section: Critique Of Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…IL10 is located on chromosome 1q31.1 and functions as a cytokine inhibitory factor decreasing the synthesis of proinflammatory molecules [Stampfli et al, 1999]. IL10 reduces IL4 and IL5 expression as well as IgE titers and eosinophil rates [Moore et al, 1993;van Scott et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylactic symptoms (activity, bristly hair, and cyanosis) were evaluated 30 min after the challenge using a scoring system modified from previous reports [29,30]. Reactions severity was classified in following categories depending on their gravity: i) (-) absent; ii) (+) weak; iii) (++) moderate; and iv) (+++) strong, and the mobility was classified in i) low or ii) normal, depending on the activity of the animals.…”
Section: Evaluation Of Anaphylaxismentioning
confidence: 99%